Preparation of 2D Tungsten Diselenide (WSe2) thin films by selenization of DC-sputtered W precursors - Mwakyusa, Lwitiko P. (Tanzania Journal of Science, 2024)
Two-dimensional layered transition metal dichalcogenides based on WSe2 films demonstrated promising properties for nano-electronics and photovoltaic applications. In this work, WSe2 films were prepared by selenization of DC-sputtered W precursors. The influence of the selenization temperature on the structural, morphology, and optical properties of the WSe2 films was investigated. The selenization temperature was varied from 350 °C to 450 °C at the interval of 50 °C. Structural, morphology and optical properties of the WSe2 were investigated using X-ray diffractometry (XRD), Atomic Force Microscope (AFM), and UV-VIS-NIR spectrophotometer, respectively. XRD analysis revealed that all WSe2 were polycrystalline and exhibited the co-existence of c-axis perpendicular and parallel substrate texture. Samples selenized at 400 °C demonstrated strong - types of crystal orientations – perpendicular c-axis substrate texture – dominated crystal growth. The AFM images further revealed the co-existence of parallel and perpendicular crystal orientations for samples selenized at 350 °C and 450 °C. Optical measurement showed that all WSe2 samples were transparent and consisted of an excitonic peak at the wavelength of around 620 nm. The estimated bandgap values were in the range of 1.22 eV to 1.37 eV which is somewhat lower than expected – the presence of W5O14 phases is suggested to be the main cause.